2019
DOI: 10.11622/smedj.2019064
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive practice in Singapore: a cross-sectional national survey

Abstract: Electroconvulsive therapy (ECT) is a safe and effective treatment for mood disorders (1,2) and schizophrenia. (3) The mechanism of ECT is not completely understood but is likely to involve changes in cerebral noradrenaline, serotonin and dopamine activities, permeability of the blood-brain barrier and neurogenesis. (4) Common side effects include headache, myalgia and transient cognitive impairment, (5) with an estimated mortality rate of 2.4 per 100,000 treatments. (6) Many surveys have been conducted in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
(44 reference statements)
1
11
0
2
Order By: Relevance
“…In cluster one, > 51% of patients had a depressive disorder (25.7%) and BAD (25.7%), which is similar to a previous study that showed that depressed female patients were more referred to ECT. 21 The average number of ECT sessions delivered to patients in cluster two was 8.7±4.0, similar to previous studies in Asia. The average number of ECT sessions for patients with depressive disorder was 6–9 treatments.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In cluster one, > 51% of patients had a depressive disorder (25.7%) and BAD (25.7%), which is similar to a previous study that showed that depressed female patients were more referred to ECT. 21 The average number of ECT sessions delivered to patients in cluster two was 8.7±4.0, similar to previous studies in Asia. The average number of ECT sessions for patients with depressive disorder was 6–9 treatments.…”
Section: Discussionsupporting
confidence: 88%
“…A study in Singapore shows that patients’ quality of life with depression improves after receiving ECT. 21 In Oman, further research on ECT is recommended, especially regarding its effect on patients’ quality of life in each subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the largest center half of the sessions are performed in the case of schizophrenia, while at other institutions mainly in resistant depression. Other disease entities include mania, schizoaffective disorder, catatonia, and malignant neuroleptic syndrome [45]. In Japan (J) and India (I), adult patients were treated with ECT for schizophrenia (J -48.9%, I -36.5%), followed by major depression (J -37.4%, I -33.5%), catatonia (J -6.8%, I -6.2%), mania (J -4.4%, I -17.9%) and dysthymia (J -0.8%, I -2.8%) [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…The Singapore Institute of Mental Health (IMH) is the only tertiary psychiatric hospital in Singapore with 1900 inpatient beds and about 40,000 outpatients and treats about 80% of the national load of psychiatric patients. In IMH, ECT is prescribed primarily for schizophrenia (47%) with schizoaffective disorder (20.3%), depression (20.4%) and mania (6.8%) being the other major indications 15 . In 2015 IMH moved from a one-size-fits-all approach (age based dosing with bitemporal electrode placement) to an individualized seizure threshold titration based approach 31,32 with a range of electrode placements (Bitemporal, Bifrontal, Right unilateral) and pulse parameters (Brief or Ultrabrief pulsewidth) using the CARE network system to collect ECT data 33 .…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…This tragic vignette underscores the importance of not just having an ECT service but having one that can respond in a timely fashion to patient needs. While 5 of the 7 ECT services 15 in Singapore were still operational at the time of this writing, the other 2 have shut down due to lack of anaesthesia manpower while others now require case by case approval for ECT by the operating theatres.…”
mentioning
confidence: 99%